1987
DOI: 10.1177/001440298705400308
|View full text |Cite
|
Sign up to set email alerts
|

Elaborated Corrective Feedback and the Acquisition of Reasoning Skills: A Study of Computer-Assisted Instruction

Abstract: The study compared basic and elaborated corrections within the context of otherwise identical computer-assisted instruction (CAI) programs that taught reasoning skills. Twelve learning disabled and 16 remedial high school students were randomly assigned to either the basic-corrections or elaborated-corrections treatment. Criterion-referenced test scores were significantly higher for the elaborated-corrections treatment on both the post and maintenance tests and on the transfer test. Time to complete the progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 14 publications
0
16
0
1
Order By: Relevance
“…however, Rosa and leow (2004) found elaboration feedback that included auC to be no better than KR without auC. similarly, though two studies reported no difference between elaboration feedback and KCR (dempsey, litchfield, & driscoll, 1993; merrill, 1987), the other five reviewed studies making the comparison showed elaboration feedback to be more effective (Collins, Carnine, & Gersten, 1987;Gilman, 1969;Grant et al, 1982;Kim & Phillips, 1991;Pridemore & Klein, 1995). Elaboration feedback has also been shown to be more effective than KR with auC in two studies (Terrell, 1990;Waldrop et al, 1986); though dempsey et al (1993) showed no difference between elaboration feedback and KCR with auC (or KCR without auC, as already mentioned).…”
Section: Elaboration Feedbackmentioning
confidence: 94%
See 2 more Smart Citations
“…however, Rosa and leow (2004) found elaboration feedback that included auC to be no better than KR without auC. similarly, though two studies reported no difference between elaboration feedback and KCR (dempsey, litchfield, & driscoll, 1993; merrill, 1987), the other five reviewed studies making the comparison showed elaboration feedback to be more effective (Collins, Carnine, & Gersten, 1987;Gilman, 1969;Grant et al, 1982;Kim & Phillips, 1991;Pridemore & Klein, 1995). Elaboration feedback has also been shown to be more effective than KR with auC in two studies (Terrell, 1990;Waldrop et al, 1986); though dempsey et al (1993) showed no difference between elaboration feedback and KCR with auC (or KCR without auC, as already mentioned).…”
Section: Elaboration Feedbackmentioning
confidence: 94%
“…Review feedback has also been arranged by re-presenting incorrectly answered frames at the end of the instruction. several studies (albertson, 1986;Collins et al, 1987;Crosbie & Kelly, 1994, Exp. i & ii;Gilman, 1969;nagata, 1993) included review feedback in all groups, thus they are not included in this section because no comparison can be made.…”
Section: Review Feedbackmentioning
confidence: 97%
See 1 more Smart Citation
“…Fisher et al (1980) found that students who had feedback contacts with teachers during seatwork generally had 10% higher engagement rates than students who did not receive feedback. Collins, Carnine, and Gersten ( 1987) reported that both basic and elaborative feedback significantly increased students' performance on reasoning skill tasks. They also compared differential effects of two types of feedback and found that both types of feedback successfully increased student performance, but that the elaborated feedback produced the greatest skill acquisition gains.…”
Section: Academic Feedbackmentioning
confidence: 99%
“…Low 'ability or low achieving learners may benefit from more explanation in feedback (Collins, Carnine, & Gersten, 1987); however, they also need to be taught how to utilize feedback information effectively. High ability learners seem to use knowledge of results feedback more effectively than low ability learners (Hansen, 1974).…”
Section: Swanary and Evaluation Of Researchmentioning
confidence: 99%